Accelerating Resilience-Based Village Government Organizations Through the Transformational Leadership of Village Heads - Akbar Maulana; Suyono (JOURNAL OF GOVERNMENT SCIENCE, 2026)
The transformational leadership of the village head is a key factor in accelerating organizational acceleration, because it is able to encourage a shared vision, innovation, empowerment of apparatus, and increased work commitment. The urgency of this research lies in the lack of empirical studies on how transformational leadership can be a catalyst for building resilience in village government organizations, especially in Kalisat Village, Kalisat District, Jember Regency. This study aims to: (1) analyze the forms and practices of transformational leadership of the village head in encouraging organizational acceleration; (2) identify the level and characteristics of organizational resilience in Kalisat Village; and (3) explain the relationship between transformational leadership and strengthening organizational resilience that impacts the improvement of village government service performance. The research uses a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and review of village planning and evaluation documents. The analysis technique uses a data reduction model, data presentation, and conclusion drawing to understand leadership patterns and organizational resilience dynamics holistically. This study also considers the local social and cultural context of Kalisat Village, including how interactions between village actors, local political dynamics, and community participation contribute to shaping the adaptive capacity of village government organizations. The research outputs include: (1) mapping the transformational leadership model of the head of Kalisat Village; (2) description of the resilience profile of the village government organization; (3) formulation of a resilience-based organizational acceleration model; (4) practical recommendations for village governments and policy makers regarding strengthening leadership capacity and organizational resilience; and (5) theoretical contributions to the development of governance studies, particularly on the issue of organizational resilience and leadership at the village level.